Sistem Informasi Pengarsipan Instrumen Akreditasi Perguruan Tinggi - Febriadi, Bayu; Wiza, Fana; Putra, Pandu Pratama (STIKOM Tunas Bangsa Pematangsiantar, 2019)
At Lancang Kuning University, there were no facilities that could be used in the preparation of university accreditation instruments, while the need for accreditation data was greatly needed by the academics of the yellowish university in the preparation of accreditation instruments for universities and study programs so that they were still having difficulty filing and presenting form data information, plans strategic and operational and self-evaluation plan along with the documents needed during the visitation activity by the assessor of the National Accreditation Board of Higher Education (BAN-PT). With the use of information technology in the application of computerized based applications for filing and presenting accreditation data needs, it is expected to help the academic community more quickly and precisely in the data processing instrument for accreditation. It is expected that with the development of archiving applications and the presentation of accreditation instruments with the completion of the System Development Lyfe Cycle (SDLC) method in the problem analysis phase, the applications built can improve the quality of accreditation instruments in data processing that are well integrated and can be utilized at any time by the community the Lancang Kuning university.